Mudanças climáticas na prática brasileira de avaliação ambiental estratégica - Nadruz, Veronica do Nascimento (2015)
The evaluation of the extent of the issue of climate change through the Strategic Environmental Assessment (SEA) has been the subject of research at the International Academy, with a view to the requirement of the Sea and the need to meet the greenhouse gas reduction targets (GHG) in European countries. In Brazil, the Sea is not mandatory and experiences with the use of the instrument are rare in the country, known only about 40 SEA reports. Regarding climate change, although the national commitments to reduce emissions across the world are few, the country has been structuring in the public and private sector to face its consequences: in 2009 we established the National Climate Change Policy that among a number of resolutions and guidelines for 2020 provides a reduction in the emission of greenhouse gases by 36.1% to 38.9%. In this context, this research has as main objective to analyze the issue of climate change in the Brazilian practice of SEA applied to national planning (energy, regional development, transport and tourism). Thus, we selected 35 studies of SEA from the 40 studies known in the country. As a method was adopted and tested a published script, the criterion proposed by Wende et al. (2011), and performed the analyzes under four perspectives: 1) individual of each SEA report; 2) comparative between different categories of planning; 3) time on the legal framework of the promulgation of National Climate Change Policy and 4) overall on the scope of climate change in the practice of Brazilian SEA. The survey results show that, in general, the transport sector is the best performer among the four categories analyzed, as 8 out of 10 reports of this sector considered climate issues. The research also concludes that in Brazil the issue of climate change is not widely considered in national planning subsidized by the SEA.